Fabrication, Characterization And Application Of Polyhydroxybutyrate-Titanium Dioxide Nanocomposite Materials - Appan, Nanthini Sridewi (2012)
A serious need for a robust, low-cost and eco-friendly method to treat dye pollutants released by textile industries motivated this research. The dye adsorption effect of biodegradable poly-3-hydroxybutyrate [P(3HB)] and the photocatalytic degradation ability of inert titanium dioxide (TiO2) was exploited to fabricate a multifunctional nanocomposite film via solvent casting and electrospinning. The environmental degradation of the choice material, cast P(3HB) was first tested and confirmed to be comparable to its co-polymers; poly(3-hydroxybutyrate-co-5 mol% 3-hydroxyvalerate) [P(3HB-co-5 mol% 3HV)] and poly(3-hydroxybutyrate-co-5 mol% 3-hydroxyhexanoate) [P(3HB-co-5 mol% 3HHx)]. The weight loss was almost complete by 8 weeks in tropical mangrove sediment. The nanocomposite film was also degradable although to a lesser extent despite the microbial inactivation effect of TiO2. The optimum amount of P(3HB) and TiO2 loading in cast film was found to be 0.4 g and 40 wt% respectively. This film had an even distribution of TiO2 when mixed concurrently in chloroform followed by stirring for 24 h. It completely decolorized and detoxified real industrial Batik dye wastewater in 3 h and induced a chemical oxygen demand (COD) reduction of 80%. The 0.4 g P(3HB)-40 wt% TiO2 film exhibited good stability with decolorization percentage of ≥80% even after the sixth repeated usage.